FIRM VALUE: A LITERATURE STUDY - Hakim, Mesra Berlyn; Dilasari, Aranta Prista (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of this research is to provide an academic review of the literature concerning the factors that impact firm value, which is considered a gauge of management performance success and has implications for investor perceptions. The research method utilized in this research is a systematic literature review. The research data were obtained through an internet search on firm value journals published between 2016 and 2019, using keywords such as "firm value," "value of firm," and "nilai perusahaan". A total of 21 journals were analyzed in this research. The data were qualitatively analyzed. The findings of the research reveal thirteen factors that influence firm value. These factors include asymmetric information, enterprise risk management, firm size, profitability, capital structure, financial performance, eco-efficiency, default risk, board reform, sustainability reporting, corporate social responsibility, tax planning, and sustainability reporting awards